Growing Healthy : A Review of Vietnam's Health Sector - World Bank (Washington, DC, 2013)
Recently, the Ministry of Health formulated its strategic directions for the period 1998-2000, whose key objectives for the health sector are: improved health status, as reflected by morbidity, and mortality reductions; greater access to public health services, especially the poor; and, increased quality, and cost-effectiveness of health services. This raises a number of policy questions, such as: which priorities will likely reduce poverty? What are the emerging roles of government, donors, and nongovernmental organizations in the financing of health services? What is the level of resources, currently available to the health sector? How can public spending be oriented to meet the strategic objectives of the Ministry of Health? This report attempts to conduct an analysis of empirical trends in, and patterns of health services utilization, health outcomes, public health expenditures, and provision of health services, and, discuss the empirical findings of the analysis. The broad objectives of the report are to: document changes in health outcomes, and health services utilization, private/public health spending, and provision of public, and private health services during the last seven years; and, identify the causes, and factors influencing these changes. Policy responses to the analysis are not provided in this report. Rather, the information is provided in the expectation that interested parties will find it useful for future policy deliberations.